A revision of the genus Isotomurus (Collembola: Isotomidae) in northern Iran using molecular evidence - Lafooraki, Elham Yoosefi; Hajizadeh, Jalil; Shayanmehr, Masoumeh (Zootaxa, 2023)
Three new species of Isotomurus Börner are described from northern Iran. Status of studied populations is confirmed as new species by using COI and 28SrRNA markers. The new species belong to species-group characterized by 3,3,1 trichobothria on Abd. II–IV, 3+3 laterodistal setae on ventral tube, and no seta on mucro. Isotomurus hyrcanicus sp. nov. is similar to I. palustris Müller in color pattern, but has two lateral bands on last abdominal segments and 10–13 setae on retinaculum. Results of COI analyses shows that all color forms in population of the new species are conspecific. Isotomurus potapovi sp. nov. has a dorsomedial band from Th. II to Abd. V and 6–7 setae on retinaculm, and Isotomurus katule sp. nov. has a uniform body color and 5–8 setae on retinaculum. An identification key for recorded species of genus Isotomurus in Iran is provided. Color pattern as a common character used to identify Isotomurus species is not always reliable and its efficiency needs to be verified for each species.